KEHIDUPAN NELAYAN PEREMPUAN ( studi kasus perempuan nelayan di Desa Kote, Kecamatan Singkep Pesisir, Kabupaten Lingga , Kepulauan Riau) - Bedy Kurnia; T Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In this study the author uses descriptive type. Sampling technique used purposive sampling. Primary data obtained by observation (observation) and using an interview guide. Data analysis techniques using qualitative methods. Population and sample in this study were the wives of fishermen who work in the village Kote Singgkep Pesisir subdistrict. This study bertujyan to know the life of fisherman's wife in running a family function. The usefulness of this research are expected results of this research into a particular input Lingga regency government in developing the potential of existing sea to the area and expected progress of this research also became a reference and comparison to other researchers associated with the study. Research results generally show that life fisherman's wife in running a family function going well, although in doing a lot of experience constraints. Where the fisherman's wife worked in the informal sector that do not require higher education and skills.Keywords ; Fisher women, Live of Fisherwomen, and Stategy of Fisherwomen